The Application of the HIRARC Method to Stone Cut Workers in Laicici, Kangeli Village, East Sumba Regency - Yunita Lende Bussa; Noorce Ch Berek; Agus Setyobudi (Universitas Nusa Cendana, 2022)
The HIRARC (Hazard Identification Risk Assessment and Risk Control) is a method of identification, hazard analysis, risk control, and the application of controls used to review processes or operations on a system. This type of research was qualitative with an in-depth interview technique, which was then summarized in a transcript and analyzed using a research form and a risk assessment matrix. This research was conducted in Laicici, Kangeli Village, Lewa Tidahu District, East Sumba Regency. Informants in this study were workers at the stone cutting site, as many as six. Determining the informants in this study used a purposive sampling technique. The results showed that each stage of work undertaken to produce a stone ready for use at the Laicici stone cutting site, Kangeli Village, had different dangers and risks. The low-risk level was the risk of falling and hearing loss. The moderate risk was a pain in the lower back and being pinched and crushed by stones. High risk was found in the risk of slipping, fatigue, working time > 8 hours per day, dehydration and heat-related illness, and the risk of eye irritation. The extreme risk was the risk of fatigue caused by working more than 8 hours every day and the risk of injury caused by sharp work tools. Controls that can be carried out to reduce or eliminate the hazards and risks at the stone cutting site for stone cutting workers are substitution, administrative control, engineering control, and the use of self-protective gears